ANALISIS MAJAS DALAM LIRIK LAGU HINGGA UJUNG WAKTU KARYA EROSS CANDRA - Siswanti Puji Lestari; Syaima Nur Amalia; Sary Sukawati (IKIP Siliwangi, 2019)
Any lyrics in the song must have a specific purpose that wish to be conveyed to his listeners. Therefore, every song lyrics will be delivered with an interesting language. The writing of the song lyrics will not regardless of the style of the language poets includes either word choice or sentence structure, diction, or figure of speech. This research will describe the figure of speech which featured in the lyrics of the song